Risk factors associated with death or neurological deterioration among patients with Gram-negative postneurosurgical meningitis. (June 2016) - Neuberger, A.; Shofty, B.; Bishop, B.; Naffaa, M.E.; Binawi, T.; Babich, T.; Rappaport, Z.H.; Zaaroor, M.; Sviri, G.; Yahav, D.; Paul, M.
Abstract: In a retrospective cohort of 115 patients with Gram-negative postneurosurgical meningitis, factors associated with 30-day mortality or neurological deterioration on multivariate analysis included days from admission to meningitis (OR 1.05 per day, 95% CI 1.02–1.09), decreased level of consciousness (OR 2.69, 95% CI 0.99–7.31), blood glucose level >180 mg/dL (OR 3.70, 95% CI 1.27–10.77), higher creatinine level (OR 4.07 per 1 mg/dL, 95% CI 1.50–11.08), and cerebrospinal fluid glucose <50 mg/dL (OR 5.02, 95% CI 1.71–14.77) at diagnosis. A predictive score triaged patients into three groups with low (4/44, 9.1%), intermediate (16/38, 42.1%) and high (22/33, 66.7%) unfavourable outcome rates. Validation on a different group of 36 patients with Gram-negative postneurosurgical meningitis was acceptable.